TEMPERATURE AND HUMIDITY INSTRUMENTATION PRACTICUM REPORT USING ARDUINO WITH DHT 11 SENSOR - Yosafat Cauvain; Tito Aviandi; Paduloh Paduloh (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The extreme temperatures that occur in Indonesia mean that we must always maintain room temperature which has an effect on body temperature. A room temperature that is too high will cause the body to release a lot of fluids which can result in dehydration, while a body temperature that is too low can make it difficult for the body to move and make the body stiff. Therefore, in this study the aim is to create an automatic room temperature accompanied by humidity. The room is equipped with an Arduino which functions like a thermometer. In this practicum, it is about temperature and humidity instrumentation using the DH11 sensor. The components used are the DHT11 sensor, Arduino Uno, jumper cables and others. Data taken during the practicum this is 3 pieces of data. This test also produces output, namely DHT 11 and a laptop to display the output results via the Arduino module. Sensor output is displayed in real time. To display the temperature in this Arduino sketch, you can open it in the Arduino IDE application